2003
DOI: 10.1104/pp.103.028563
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Arabidopsis Arp2/3 Complex Controls Leaf Cell Morphogenesis  

Abstract: The evolutionarily conserved Arp2/3 complex has been shown to activate actin nucleation and branching in several eukaryotes, but its biological functions are not well understood in multicellular organisms. The model plant Arabidopsis provides many advantages for genetic dissection of the function of this conserved actin-nucleating machinery, yet the existence of this complex in plants has not been determined. We have identified Arabidopsis genes encoding homologs of all of the seven Arp2/3 subunits. The functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
193
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 51 publications
10
193
1
Order By: Relevance
“…The SCAR/WAVE complex and the downstream Arp2/3 complex form a conserved actin regulatory module in most plants (Deeks et al ., 2004; Yanagisawa et al ., 2013), and each is composed of multiple functional subunits (Li et al ., 2003). To determine whether mutations in other subunits caused defects in stomatal behaviour in the dark, we performed stomatal bioassays on a subset of mutants of the two protein complexes that were previously shown to display aberrant actin cytoskeletons.…”
Section: Resultsmentioning
confidence: 99%
“…The SCAR/WAVE complex and the downstream Arp2/3 complex form a conserved actin regulatory module in most plants (Deeks et al ., 2004; Yanagisawa et al ., 2013), and each is composed of multiple functional subunits (Li et al ., 2003). To determine whether mutations in other subunits caused defects in stomatal behaviour in the dark, we performed stomatal bioassays on a subset of mutants of the two protein complexes that were previously shown to display aberrant actin cytoskeletons.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the moss Physcomitrella patens, loss of one of the ARP2/3 subunits completely blocks the tipgrowth of caulonemal cells and thus prevents bud formation and the development of leafy gametophores [36]. Several authors have noted that ARP2/3 mutants have less fine cortical actin and more thick endoplasmic actin cables, and have suggested that fine cortical actin plays a role in cell expansion [16,34,37 ]. It will presumably take ultrastructural investigation to reveal how fine actin that is established by ARP2/3 differs from that established by other regulators, such as formin.…”
Section: Coordination Of Microtubules and Actin In Cells With Complexmentioning
confidence: 99%
“…Homologs of all seven subunits of the ARP2/3 complex have now been identified in plants on the basis of homology searches and loss-of-function mutants [30 , [33][34][35]. Mutations in the ARP2/3 complex of Arabidopsis cause abnormal actin organization and deformation of trichomes, leaf epidermal pavement cells and some hypocotyl epidermal cells, but overall plant morphology is scarcely affected.…”
Section: Arp2/3 Complexmentioning
confidence: 99%
“…However, knocking out the Arp2/3 complex has no effects on pollen tube growth, suggesting an Arp2/3 complex independent mechanism is involved in the assembly of the tip actin (Li and Yang, unpublished data). Similarly, ROP2-dependent cortical diffuse F-actin remains in the pavement cells of Arabidopsis leaves defective in the Arp2/3 complex [66]. As discussed below, in both pollen tubes and pavement cells, the assembly of cortical F-actin is activated by a plant-specific ROP effector protein, RIC4.…”
Section: Plant Rop Vs Animal Rho Effectors and Downstream Processesmentioning
confidence: 95%
“…However, Arabidopsis homologs of the Arp3 and ArpC2 subunits were able to complement mutants for the corresponding genes in yeast [60,61]. Mutants of Arabidopsis ARP2, ARP3, APRC2a, ARPC5, NAP1 and PIR121/SRA1, as well as BRK1 RNAi plants, all show highly similar phenotypes, characterized by cell [46,[60][61][62][63][64][65][66][67][68]. Furthermore, T-DNA knockout mutants for one of four Arabidopsis WAVE/SCAR homologs show similar, but milder phenotypes [69,70].…”
Section: Plant Rop Vs Animal Rho Effectors and Downstream Processesmentioning
confidence: 99%